Development of a tool to describe the role of the clinical nurse consultant in Australia. Issue 11 (17th September 2012) - Fry, Margaret; Duffield, Christine; Baldwin, Richard; Roche, Michael; Stasa, Helen; Solman, Annette
<x xml:space="preserve">Abstract</x> Aims and objectives. To develop a tool for defining and measuring the role characteristics and responsibilities of an advanced practice nursing role in Australia. Background. Internationally, there is considerable confusion about the precise role responsibilities of advanced practice nursing positions. In Australia, the clinical nurse consultant is an advanced practice role with five nominated domains of practice. However, there are no tools for measuring the performance of clinical nurse consultants against the listed domains. Design and methods. Participants were 56 clinical nurse consultants at a tertiary public hospital. The existing literature, an online survey, and position descriptions were used to generate the a priori themes for the initial template. Semi‐structured interviews were conducted (in 2010) to test the template characteristics. The template underwent multiple iterations in its development. Results. A 50‐item tool was devised, which consisted of five domains with a ten‐point hierarchical scale within each domain. In preliminary testing, the revised template was found to provide greater clarity regarding roles and grades than the original position descriptions. Conclusions. Further testing and refinement of the modified rating scale is needed, but it offers the possibility of a new tool that can be used by health service managers to determine the grade of a clinical nurse consultant position and for evaluating role performance. Relevance to clinical practice. This preliminary study suggests that the tool provides a useful means of measuring advanced nursing practice and responsibilities across different domains and levels of appointment. The tool may be able to be adapted for use with other advanced practice nursing roles both within Australia and internationally.